A DFT investigation of CO adsorption on VIIIB transition metal-doped graphene sheets - Wanno, Banchob; Tabtimsai, Chanukorn (Superlattices and microstructures, 2014)
Adsorptions of CO on pristine, Fe-, Ru-, Os-, Co-, Rh-, Ir-, Ni-, Pd-, and Pt-doped graphene were theoretical investigated. Transition metal doped graphenes were more highly sensitive to CO adsorption than that of pristine graphene. •Adsorptions of CO on pristine and transition metal doped graphene were investigated by using a DFT method.•Transition metal doped graphenes can improve CO adsorption ability of pristine graphene.•The system of Os-doped graphene sheet was found to be the most sensitive to CO molecule.•Structural and electronic properties of adsorption complexes were reported. Adsorptions of CO on pristine, Fe-, Ru-, Os-, Co-, Rh-, Ir-, Ni-, Pd-, and Pt-doped graphene were investigated, using density functional theory calculation at B3LYP/LanL2DZ theoretical level. This work revealed that the transition metal doped graphenes were more highly sensitive to CO adsorption than that of pristine graphene. The Os- and Fe-doped graphenes displayed the strongest interaction with C and O atoms of CO molecule, respectively.